2020
DOI: 10.1001/jama.2020.16195
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Catheter Ablation With Vein of Marshall Ethanol Infusion vs Catheter Ablation Alone on Persistent Atrial Fibrillation

Abstract: IMPORTANCE Catheter ablation of persistent atrial fibrillation (AF) has limited success. Procedural strategies beyond pulmonary vein isolation have failed to consistently improve results. The vein of Marshall contains innervation and AF triggers that can be ablated by retrograde ethanol infusion. OBJECTIVE To determine whether vein of Marshall ethanol infusion could improve ablation results in persistent AF when added to catheter ablation. DESIGN, SETTING, AND PARTICIPANTS The Vein of Marshall Ethanol for Untr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
201
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(249 citation statements)
references
References 22 publications
5
201
1
Order By: Relevance
“…Reported complications of VOM-EI include vascular access complications, pericardial effusion, pericarditis, VOM dissection and volume overload. 10,11,13 In our population of patients with intended VOM-EI, we observed pericardial effusion/pericarditis in four patients (18%) and VOM dissection in two (9%), all of which resolved without additional interventions. We performed echocardiography the day after VOM-EI in 86% of patients, irrespective of symptom status.…”
Section: Feasibility and Safety Of Vom-eimentioning
confidence: 76%
See 1 more Smart Citation
“…Reported complications of VOM-EI include vascular access complications, pericardial effusion, pericarditis, VOM dissection and volume overload. 10,11,13 In our population of patients with intended VOM-EI, we observed pericardial effusion/pericarditis in four patients (18%) and VOM dissection in two (9%), all of which resolved without additional interventions. We performed echocardiography the day after VOM-EI in 86% of patients, irrespective of symptom status.…”
Section: Feasibility and Safety Of Vom-eimentioning
confidence: 76%
“…10 Other groups reported successful VOM-EI rates of 73.4-92%. 11,13,14 . Using the same approach, we successfully achieved VOM-EI in comparable 86% of cases.…”
Section: Feasibility and Safety Of Vom-eimentioning
confidence: 99%
“…Initial attempts were performed to modulate AF induction by parasympathetic responses elicited through high‐frequency stimulation in the ligament of Marshall, which were successfully abolished by ethanol injection (Table 3). 101 The first randomized controlled clinical trial in patients with persistent AF undergoing their first catheter ablation has recently reported that the addition of vein of Marshall ethanol infusion to catheter ablation, compared with catheter ablation alone, increased the likelihood of remaining free of AF or atrial tachycardia at 6 and 12 months (49.2% vs. 38% after a single procedure) 102 . The MARS‐AF trial (vein of Marshall ethAnol for Recurrent perSistent AF) is another randomized controlled study currently on‐going in patients with persistent AF, including also patients with prior ablation.…”
Section: Anatomically Based Approaches Beyond the Pulmonary Veinsmentioning
confidence: 99%
“…In case of symptomatic persistent AF recurrences, it would be reasonable to move forward to a third step and target other anatomical regions that have been potentially associated with AF maintenance as mitral isthmus, cardiac ganglia, ligament of Marshall, atrial scar regions, and LAA (Figure 3B). In this context, point‐by‐point RF delivery still represents the most accredited strategy, 69,78,106,107,119,120 with the exception of the ligament of Marshall and the LAA, for which direct ethanol injection in the vein and cryoballoon ablation, 102,109 respectively, have shown to be an effective way to achieve rapid ablation of such regions.…”
Section: Implications For Clinical Practice and Conclusionmentioning
confidence: 99%
“…However, most of these initially‐promising strategies have failed to show benefit in multicenter randomized trials 1,7 . Furthermore, methods that have shown additional benefit over PVI in multicenter RCTs may raise the risk of procedural or postprocedure complications (as in the case of hybrid surgical ablation or left atrial appendage isolation) or require a different skillset while still leaving a relatively large proportion of patients with recurrence (vein of Marshall ethanol injection) 8–12 …”
mentioning
confidence: 99%